Lapland longspur mortality at an oil well drilling rig site, Laramie County, Wyoming. (13th October 2014) - Ramirez, Pedro; Dickerson, Kimberly; Lindstrom, Jim; Meteyer, Carol U.; Darrah, Scott
ABSTRACT: Two hundred fifty‐one Lapland longspur ( Calcarius lapponicus ) carcasses were recovered around an oil well drilling rig in Laramie County, Wyoming, USA, on December 13–14, 2010, apparent victims of a winter storm and "light entrapment" from the lights on the drilling rig during foggy conditions. We found Lapland longspur carcasses distributed around the drilling rig from 33 m to 171 m. Investigators did not find evidence of bird carcasses on the drilling rig deck or equipment immediately adjacent to the drilling rig. We ruled out chemical toxins and disease as a cause of mortality. Weather conditions, the circular depositional pattern of carcasses around the drilling rig, and bird necropsy results led investigators to conclude that the Lapland longspur mortality was the result of the migrating birds entering the area illuminated by the drilling rig lights in freezing fog and the birds repeatedly circling the drilling rig until they fell to the ground in exhaustion and dying from subsequent trauma. Further research is needed to understand how to most effectively adjust lighting of onshore drilling rigs to reduce the potential for avian light entrapment. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.